A Technical Review on IMC-PID Design for Integrating Process With Dead Time - K. Divakar; M. Praveen Kumar; Dhanamjayulu C; Gokulakrishnan G (IEEE Access)
The demeanour of many chemical and non-chemical processes resemble that of an integrating process. Developing a control plan for an integrating process is complicated, and the difficulty becomes even more when dead time is present. Internal Model Control (IMC) is enthralling in the creation of control strategies because it can derive the controller in the framework of a Proportional-Integral-Derivative controller (PID). It has been noted that when a filter is added to a controller, its performance improves, and various researchers have proposed PID with filter. The current work presents a comprehensive review of existing IMC-PID controllers for controlling integrating processes with dead time. The filter postulation in IMC is discussed, which is responsible for generating several forms of PID for the same process. Performance is measured using a variety of conventional performance indices. This article provides an overview of IMC filter topologies used in IMC-PID tuning for various integrating processes, including tuning relations and time delay approximations. The paper has also highlighted the guidelines for the selection of IMC filter and different structures of IMC filters from conventional to fractional order.